2017
DOI: 10.1016/j.crwh.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Intracavitary deposits on Essure® hysteroscopic sterilization devices: A case report

Abstract: ObjectiveTo study the composition of intracavitary deposits on Essure® hysteroscopic sterilization devices.DesignCase report.SettingReproductive Medicine and Gynecology department of a University Hospital.Patient(s)A 39 years old patient presenting with a request for surgical removal of Essure® sterilization devices. Diagnostic hysteroscopy showed a crystal like white deposit attached to one of the devices.InterventionDiagnostic hysteroscopy and surgical removal of Essure® devices was performed. The deposits w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Ongoing symptoms are displayed as percentages of the total together with the initial percentages of patients experiencing the symptoms. research showed this to be calcite [11]. However, the exact meaning of this phenomenon remains unclear.…”
Section: Discussionmentioning
confidence: 98%
“…Ongoing symptoms are displayed as percentages of the total together with the initial percentages of patients experiencing the symptoms. research showed this to be calcite [11]. However, the exact meaning of this phenomenon remains unclear.…”
Section: Discussionmentioning
confidence: 98%
“…The clinical significance of calcium deposits on the Essure device has not been established. Maassen et al [6] reported a case of deposits on an Essure device that on chemical analysis resulted in calcite (calcium carbonate, CaCO 3 ). Metal corrosion and inflammation had been reported as the possible cause of crystal formation on copper intrauterine devices.…”
mentioning
confidence: 99%